Perinatal Nutritional and Metabolic Pathways: Early Origins of Chronic Lung Diseases - Kuiper-Makris, Celien; Selle, Jaco; Nüsken, Eva; Dötsch, Jörg; Alejandre Alcazar, Miguel A. (Frontiers in Medicine, 2021)
Lung development is not completed at birth, but expands beyond infancy, rendering the lung highly susceptible to injury. Exposure to various influences during a critical window of organ growth can interfere with the finely-tuned process of development and induce pathological processes with aberrant alveolarization and long-term structural and functional sequelae. This concept of developmental origins of chronic disease has been coined as perinatal programming. Some adverse perinatal factors, including prematurity along with respiratory support, are well recognized to induce bronchopulmonary dysplasia (BPD), a neonatal chronic lung disease that is characterized by arrest of alveolar and microvascular formation as well as lung matrix remodeling. While the pathogenesis of various experimental models focus on oxygen toxicity, mechanical ventilation and inflammation, the role of nutrition before and after birth remain poorly investigated. The present review provides a comprehensive overview of the impact of perinatal malnutrition, obesity and metabolic syndrome on metabolic programming of lung structure and function. There is accumulating clinical and experimental evidence that intrauterine growth restriction (IUGR) as a consequence of limited nutritive supply due to placental insufficiency or maternal malnutrition is a major risk factor for BPD and impaired lung function later in life. In contrast, a surplus of nutrition with perinatal maternal obesity, accelerated postnatal weight gain and early childhood obesity is associated with wheezing and adverse clinical course of chronic lung diseases, such as asthma. While the link between perinatal nutrition and lung health has been described, the underlying mechanisms remain poorly understood. There are initial data showing that inflammatory and nutrient sensing processes are involved in programming of alveolarization, pulmonary angiogenesis, and composition of extracellular matrix. Here, we revise the current knowledge regarding the impact of perinatal metabolism and nutrition on the lung and beyond the cardiopulmonary system as well as possible mechanisms determining the individual susceptibility to CLD early in life. We aim to emphasize the importance of unravelling the mechanisms of perinatal metabolic programming to develop novel preventive and therapeutic avenues.